Multilocus analyses of an Antarctic fish species flock (Teleostei, Notothenioidei, Trematominae): phylogenetic approach and test of the early-radiation event - Janko, Karel; Marshall, Craig; Musilová, Zuzana; Van Houdt, Jeroen; Couloux, Arnaud; Cruaud, Corinne; Lecointre, Guillaume (Molecular phylogenetics and evolution, 2011)
Clades that have undergone episodes of rapid cladogenesis are challenging from a phylogenetic point of view. They are generally characterised by short or missing internal branches in phylogenetic trees and by conflicting topologies among individual gene trees. This may be the case of the subfamily Trematominae, a group of marine teleosts of coastal Antarctic waters, which is considered to have passed through a period of rapid diversification. Despite much phylogenetic attention, the relationships among Trematominae species remain unclear. In contrast to previous studies that were mostly based on concatenated datasets of mitochondrial and/or single nuclear loci, we applied various single-locus and multilocus phylogenetic approaches to sequences from 11 loci (eight nuclear) and we also used several methods to assess the hypothesis of a radiation event in Trematominae evolution. Diversification rate analyses support the hypothesis of a period of rapid diversification during Trematominae history and only a few nodes in the hypothetical species tree were consistently resolved with various phylogenetic methods. We detected significant discrepancies among trees from individual genes of these species, most probably resulting from incomplete lineage sorting, suggesting that concatenation of loci is not the most appropriate way to investigate Trematominae species interrelationships. These data also provide information about the possible effects of historic climate changes on the diversification rate of this group of fish.
Keywords: Sequence Analysis, DNA; vznik druhů (genetika); Animals; Phylogeny; Bayesova věta; zvířata; sekvenční analýza DNA; Fishes; fylogeneze; Bayes Theorem; Antarktida; Genetic Speciation; Antarctic Regions; ryby